Territories of panic as rhizomatic narratives of the megathrust threat in CNBC reporting - Christantyawati, Nevrettia; Maarif, Syamsul; Priyanto; Harwiki, Wiwiek; Yahya, Ardiansyah Saifuddin (Masyarakat, Kebudayaan dan Politik, 2026)
This study critically examines how the discourse of megathrust earthquake threat in Java, Indonesia, is constructed and circulated by CNBC Indonesia’s online news coverage. Given Indonesia is extremely vulnerable to the earthquake, this study explores how fear narratives are constructed and disseminated, revealing a discursive landscape for signaling panic, uncertainty and technocratic authority. Employing Van Dijk’s social cognition framework and Deleuze’s rhizomatic theory, the research reveals how information about the megathrust danger multiplied in fragmented, nonlinear ways that created dispersed nodes of public anxiety. The findings indicate that the media’s use of apocalyptic rhetoric and sensationalist framing transforms scientific caution into a hyperreal spectacle, distorting the actual meanings of official statements from The Meteorology-Climatology, Geophysics Agency and producing public “Panic Territories.” This distortion sustains the dominance of expert-driven discourse whilst marginalizing local community knowledge and active public participation. The study argues for a more reflective and participatory model of disaster journalism that emphasizes public preparedness, psychological resilience, critical literacy, and inclusive communication practices. By shifting disaster narratives away from fear based clickbait toward empowerment and preparedness, media can serve as agents of social learning and collective safety rather than amplifiers of panic.